Jilbab Konstruksi Makna Jilbab Sebagai Simbol Komunikasi Sosial Masyarakat Urban: Studi Pada Miss Hijab Banten - Baedowi, Ahmad; Gumelar, Rangga Galura (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
This in-depth study investigates the social construction of the hijab as a symbol of social communication in the context of urban society by exploring the unique experiences and perspectives of Miss Hijab Banten. With a theoretical framework based on Peter L. Berger and Thomas Luckman's theory of social construction, this research employs the externalization, objectivation, and internalization approach to understand how the meaning of the hijab is formed and accepted in social interactions. The research highlights the remarkable role of Miss Hijab Banten, who not only represents beauty but also acts as an agent of social change. They actively reconceptualize the meaning of the hijab, proving that it is not just clothing but an empowerment tool capable of breaking stereotypes and creating opportunities for Muslim women in the dynamic urban society. The study not only presents findings related to society's perceptions of the hijab but also integrates social construction theory with George Herbert Mead's symbolic interaction approach. This provides deeper insights into how social identity influences the acceptance of the hijab in urban society. The implications of the findings emphasize the need to re-adapt the meaning of the hijab in a continually changing society. Keywords: Hijab, Social Construction, and Miss Hijab Banten